2021
DOI: 10.1186/s12891-021-04300-x
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopy‐controlled medial reefing and lateral release for recurrent patellar dislocation: clinical, radiologic outcomes and complications

Abstract: Background Few studies have reported the clinical outcomes of the medial reefing procedure and lateral release with arthroscopic control of medial retinacular tension in patients with recurrent patellar dislocation. The purpose of this study was to investigate the clinical, radiologic outcomes and complications of arthroscopy-controlled medial reefing and lateral release. Methods Patients who underwent arthroscopy-controlled medial reefing and late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
7
0
3
Order By: Relevance
“…Beck [19] in 2007 used a digital tensiometer to observe patellofemoral ligament tension on frozen cadavers and concluded that a force of 2 N would restore a good patellofemoral track and Philippot [20] that a force of 10 N would restore a good patellofemoral track, but both authors used frozen cadavers and knees that had not previously been subluxated, and therefore may not have maximised the simulate the mechanics and graft tension in patients with patellar dislocation, our inclusion criteria in the study were all patients with recurrent patellar dislocation and yielded a pre-LRR, graft tension of approximately 35 N and post-LRR, a force of approximately 24 N was required to restore a good patellofemoral track, we used observation of graft tension to observe a statistically signi cant difference in the change in pre-LRR surgery and no previous studies in the literature have preoperative graft tension, the comparison in this study could provide new data to support the study of LRR [21,22].…”
Section: Discussionmentioning
confidence: 86%
“…Beck [19] in 2007 used a digital tensiometer to observe patellofemoral ligament tension on frozen cadavers and concluded that a force of 2 N would restore a good patellofemoral track and Philippot [20] that a force of 10 N would restore a good patellofemoral track, but both authors used frozen cadavers and knees that had not previously been subluxated, and therefore may not have maximised the simulate the mechanics and graft tension in patients with patellar dislocation, our inclusion criteria in the study were all patients with recurrent patellar dislocation and yielded a pre-LRR, graft tension of approximately 35 N and post-LRR, a force of approximately 24 N was required to restore a good patellofemoral track, we used observation of graft tension to observe a statistically signi cant difference in the change in pre-LRR surgery and no previous studies in the literature have preoperative graft tension, the comparison in this study could provide new data to support the study of LRR [21,22].…”
Section: Discussionmentioning
confidence: 86%
“…In some operations, under arthroscopic observation, the joint capsule was cut through the joint and released layer by layer until the subcutaneous tissue was reached. 12 , 13 , 14 , 15 In other operations, a layer-by-layer incision was made inward with surgical instruments from outside the joint capsule, which often required the creation of a subcutaneous space. 16 , 17 , 18 , 19 , 20 , 21 All of these procedures cut open the knee joint capsule and destroyed the integrity of the joint capsule.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the achievement of significant improvements in the incidence of postoperative complications compared with open surgery, as well as functional scores such as the International Knee Documentation Committee (IKDC) score, Lysholm score, and Kujala score, postoperative patellofemoral joint instability, weakened extensor mechanism muscle strength, and intra-articular hematoma still occurred. 15 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…Non-operative approaches include medially directed tape application, nonsteroidal anti-inflammatory drugs, and exercise regimens targeting the trunk, hip, and decreased extremity muscle mass [11]. Surgical options involve arthroscopy, lateral release, and medial tissue tightening, though these have been deemed ineffective [12,13]. Current literature suggests that a majority of patients may see improvement through the use of conservative treatments [9].…”
Section: Introductionmentioning
confidence: 99%